Urinary N-acetylglucosaminidase in People Environmentally Exposed to Cadmium Is Minimally Related to Cadmium-Induced Nephron Destruction - Soisungwan Satarug (Toxics)
Exposure to even low levels of the environmental pollutant cadmium (Cd) increases the risk of kidney damage and malfunction. The body burden of Cd at which these outcomes occur is not, however, reliably defined. Here, multiple-regression and mediation analyses were applied to data from 737 non-diabetic Thai nationals, of which 9.1% had an estimated glomerular filtration rate (eGFR) ≤ 60 mL/min/1.73 m2 (a low eGFR). The excretion of Cd (ECd), and renal-effect biomarkers, namely β2-microglobulin (Eβ2M), albumin (Ealb), and N-acetylglucosaminidase (ENAG), were normalized to creatinine clearance (Ccr) as ECd/Ccr Eβ2M/Ccr, Ealb/Ccr, and ENAG/Ccr. After adjustment for potential confounders, the risks of having a low eGFR and albuminuria rose twofold per doubling ECd/Ccr rates and they both varied directly with the severity of β2-microglobulinuria. Doubling ECd/Ccr rates also increased the risk of having a severe tubular injury, evident from ENAG/Ccr increments [POR = 4.80, p = 0.015]. ENAG/Ccr was strongly associated with ECd/Ccr in both men (β = 0.447) and women (β = 0.394), while showing a moderate inverse association with eGFR only in women (β = −0.178). A moderate association of ENAG/Ccr and ECd/Ccr was found in the low- (β = 0.287), and the high-Cd body burden groups (β = 0.145), but ENAG/Ccr was inversely associated with eGFR only in the high-Cd body burden group (β = −0.223). These discrepancies together with mediation analysis suggest that Cd-induced nephron destruction, which reduces GFR and the tubular release of NAG by Cd, involves different mechanisms and kinetics.